2009
DOI: 10.1037/a0017048
|View full text |Cite
|
Sign up to set email alerts
|

Different forces, same consequence: Conscientiousness and competence beliefs are independent predictors of academic effort and achievement.

Abstract: Conscientiousness and domain-specific competence beliefs are known to be highly important predictors of academic effort and achievement. Given their basis in distinct research traditions, however, these constructs have rarely been examined simultaneously. Three studies with 571, 415, and 1,535 students, respectively, found a moderate association between conscientiousness and competence beliefs, but competence beliefs meaningfully predicted both conscientiousness and academic effort, irrespective of how academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
124
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(143 citation statements)
references
References 74 publications
11
124
3
2
Order By: Relevance
“…Thus, Trautwein, Lüdtke, Roberts, et al (2009) reported that the positive effects of ASC on subsequent school grades are mediated in part by conscientious and persistent homework effort, even after controlling for prior achievement. This would suggest that ASC should lead to increased effort, which in turn would lead to better achievement.…”
mentioning
confidence: 94%
“…Thus, Trautwein, Lüdtke, Roberts, et al (2009) reported that the positive effects of ASC on subsequent school grades are mediated in part by conscientious and persistent homework effort, even after controlling for prior achievement. This would suggest that ASC should lead to increased effort, which in turn would lead to better achievement.…”
mentioning
confidence: 94%
“…Jackson et al (2012) further contend that "narrow" self-efficacy measures do not necessarily provide better explanation of the phenomenon being predicted. They cite the findings of a study by Trautwein, Lüdtke, Roberts, Schnyder, and Niggli (2009) that includes a variable called "competency beliefs." It is measured by several traitlike items, many of which actually measure incompetent habitual behaviors, not self-belief, for example, "I often feel completely lost when doing my math homework."…”
Section: Intractable Misrepresentation Of Self-efficacy Assessmentmentioning
confidence: 99%
“…Many cases of low achievement are not related to atypical brain functioning which characterizes a learning disability. Other factors such as self-perception (Greven, Harlaar, Kovas, Chamorro-Premuzic, & Plomin, 2009), conscientiousness/effort (Trautwein, Ludtke, Roberts, Schnyder, & Niggli, 2009), and motivation (Chen & Stevenson, 1995;Shaikholeslami & Khayyer, 2006)are also known to influence school achievement, but were not assessed in this study. A recent study (Fast et al, 2010) provided evidence that the perceived classroom environment (how mastery oriented, challenging and caring it is) is related to math self-efficacy and performance.…”
Section: Discussionmentioning
confidence: 98%